Application of association rules for formation of public (administrative) services portfolio - Гавриленко, Олена Валеріївна; Хоменко, Олександр Миколайович; Жураковська, Оксана Сергіївна; Коган, Алла Вікторівна; Піскун, Андрій Михайлович; Халус, Олена Андріївна (Національний технічний університет "Харківський політехнічний інститут", 2022)
The formation of complex services is carried out exclusively according to the principle of association based on a life (business) event or situation. But as practical experience shows, users often request several services at the same time, and these services are not connected by one life event. This can be seen if you analyze the statistical data on service delivery by service delivery centers. The application of intelligent data analysis allows to reveal the hidden relationship between services. Based on this, a new principle of combining services was formulated. The object of research is the process of forming a portfolio of services based on association rules. An algorithm for forming a portfolio and providing recommendations for a decision-maker has been developed. Recommendations are presented in the form of sets of services that can be included in a portfolio. The application of this principle will allow to expand the set of complex services due to new portfolios. This will simplify and improve the service delivery process for both authorities and users.

Формування комплексу послуг здійснюється виключно за принципом об'єднання на основі життєвої (ділової) події чи ситуації. Але, як показує практичний досвід, користувачі часто запитують кілька послуг одночасно, і ці послуги не пов'язані однією життєвою подією. Це можна побачити, якщо проаналізувати статистичні дані щодо надання послуг центрами надання послуг. Застосування методів інтелектуального аналізу дозволяє виявити прихований зв'язок між послугами. На основі цього був сформульований новий принцип об'єднання послуг. Об'єктом дослідження є процес формування портфеля послуг на основі асоціативних правил. Розроблено алгоритм формування портфоліо та надання рекомендацій для особи, яка приймає рішення. Рекомендації представлені у вигляді наборів послуг, які можна включити в портфоліо. Застосування цього принципу дозволить розширити набір комплексних послуг за рахунок нових портфелів. Це спростить і покращить процес надання послуг як для органів влади, так і для користувачів.
Застосування асоціативних правил для формування портфеля публічних (адміністративних) послуг
Keywords: complex public service; principle of association by life event; service portfolio; correlation of services; association rule; комплексна державна послуга; принцип асоціації за життєвою подією; портфель послуг; асоціативні правила